Stem bending and macronutrient allocation from mutamba seedlings - Malavasi, Ubirajara Contro; Ajala, Michelle Cristina; Dranski, João Alexandre Lopes; Lana, Maria do Carmo (Scientia Agraria Paranaensis, 2024)
Seedling mineral nutrition affects the allocation of biomass to the various components above and below ground. Hardening or acclimatization via mechanical treatment has resulted in differentiated nutritional allocation among plant tissues. Guazuma ulmifolia Lamarck seedlings 90 days after sowing (DAS) were subjected to four daily frequencies of stem bending (zero, 10, 20 or 40 flexions) and evaluated for stress and macronutrient allocation.The tested treatments did not show stress induction in the seedlings when measured by the PER test but increased the calcium and magnesium contents of the stems. The use of 10 daily stem bending resulted in an increase in nitrogen concentration in stem tissues, while phosphorus concentration increased in both stem and roots. The imposition of 10 or 20 daily stem bending provided a reduction in the potassium concentration in the roots, as well as an increase in the calcium and magnesium contents in the stem.